Autism and last mile in e-commerce - Reis, Nélio Fernando dos (2024)
There are a several obstacles that can make it difficult to structure a last mile in e-commerce. The objective of this study is to identify the main challenges that impact the last mile and answer the following question: “can the restricted interest of the professional with autism spectrum disorder optimize the last mile for e-commerce? The hypothesis to be tested is that autistic professionals can bring unique and valuable skills. The methodology used followed the steps of observation, problem elaboration, bibliographical research, data tabulation through non-parametric tests, data analysis and discussions. The result found is that both customers and managers want more attention in picking, packing, and routing, giving rise to skills of restricted interest, that is, the person who focuses on it, being a technical specialist. One of the greatest virtues of the person with autism spectrum disorder (ASD) is the restricted interest.